Voicing Contrast in Tracheoesophageal Speakers - Santhosh M; Priyanka Parakh; Rajashekar B (Journal of All India Institute of Speech and Hearing, 1970)
For optimal rehabilitation, it is essential to evaluate different factors which affect the intelligibility of alaryngeal speakers. Previous studies on Tracheo Esophageal (TE) speech production have mainly focused on aspects of neo-glottal phonation, speaking rate and pausing, and have ignored the changes in other speech characteristics. One such aspect which has not been studied extensively is the voiced/unvoiced distinction. Hence, the present study investigated the voicing contrasts in TE speakers. Two groups of subjects participated in the present study. Group I consisted of six TE speakers in the age range of 45 to 70 years. Group II consisted of six age and gender matched normal laryngeal speakers. Eight meaningful bisyllabic words containing all the voiced and unvoiced plosives (velar, palatal, dental and bilabial) in Kannada, uttered by the subjectswere recorded and analyzed perceptually and acoustically. The results of the perceptual analysis revealed that, voicing contrast in TE speakers were near normal except for /p/. Acoustic analyses showed significant differences between acoustic parameters of voiced and unvoiced plosives, endorsing the view that TE speakers make use of multiple acoustic parameters for voicing contrast. The results of the present study have clinical relevance as reduced voicing contrast in case of alaryngeal speakers may indirectly reflect on intelligibility of speech.